Financial Analysis Of Students With The Application Of E-Learning - Yulyanah, Yulyanah; Kurniawati, Desi (Universitas Gorontalo, 2021)
This study aims to find out the views of students with the application of E-Learning learning during the pandemic. This research method is qualitative descriptive with the research subject of D3 Accounting students of the Faculty of Economics, Pamulang University in the 2020-2021 school year. The data was obtained from a questionnaire in the form of a goggle form given to respondents. The number of respondents who filled as many as 123 respondents.. The results of the study concluded that for online learning income there was a 6% decrease in from Rp. 1,000,000 when offline 38% to 24% when online. As for expenses - expenses that increase are utility costs, internet quota costs and consumption costs for costs that decrease when online learning is for transportation costs. From the results of the analysis of income and expenditure dominant reponden tend to choose offline or offline learning as much as 59% of respondents.